Big Nate and friends (Big Nate (Andrews McMeel Pub.), , 1, 2012)
Self-proclaimed genius Nate Wright blazes a haphazard trail through the sixth grade at P.S. 38. Nate has an unshakable belief that he is number one.

Crunch (Click, 5, 1, 2022)
"It’s no secret that Olive loves trying new things. Between taking guitar lessons, making a short film, joining Berry Scouts, and leading the charge on her school’s dress code reform, Olive has her hands full! But she enjoys being busy, so staying on track with her jam-packed schedule should be no problem…right? As weeks fly by, it gets harder and harder for Olive to find time for her activities, never mind time for herself. Will she be able to accomplish her goals, or will all her sizzle turn to fizzle?

Best Friends (Friends (Hale), 2, 1, 2019)
A National and New York Times Bestseller! The creators of Real Friends Shannon Hale and LeUyen Pham are back with a true story about popularity, first crushes, and finding your own path in the graphic novel, Best Friends. Follow your heart. Find your people. Sixth grade is supposed to be perfect. Shannon's got a sure spot in the in-crowd called The Group, and her best friend is their leader, Jen, the most popular girl in school. But the rules are always changing, and Shannon has to scramble to keep up. She never knows which TV shows are cool, what songs to listen to, and who she's allowed to talk to. Who makes these rules, anyway? And does Shannon have to follow them? A School Library Journal Best Book of 2019 A Chicago Public Library Best of the Best Book of 2019 A National Public Radio (NPR) Best Book of 2019 One of NBC Today's 26 Best Kids' Books of 2019 2020 Bank Street College of Education Best Children's Books of the Year List

Freestyle (Graphix, an imprint of Scholastic, Scholastic Inc., 2022)
"Cory’s dance crew is getting ready for a major competition. It’s the last one before they graduate eighth grade and go their separate ways to high schools all over New York City, so they have to make it count! But the group starts to have problems as their crew captain gets increasingly intense about nailing the routine, and things go from bad to worse when Cory’s parents ground him for not taking his grades seriously. He gets stuck with a new tutor, Sunna, who he dismisses as a boring nerd…until he catches her secretly practicing cool yo-yo tricks. Cory wants to learn the art of yo-yo, and as his friendship with Sunna grows, he ends up missing practice and bailing on his crew—and they are not happy about it. With mounting pressure coming from all sides, how is Cory supposed to balance the expectations of his parents, school, dance, and his new friend?" --Publisher.

Big Nate: the gerbil ate my homework (Big Nate (Andrews McMeel Pub.), , 1, 2020)
"You've got to know where you stand to survive sixth grade, and Nate Wright's found the perfect spot: right next to Sherman, the class gerbil. Can Nate's furry friend bail him out of his latest homework jam with Mrs. Godfrey? Or will there be a paper trail leading straight to detention?" -- back cover The thrilling next installment in the enormously popular Big Nate series. Dating an older lady has its challenges, and Nate isn't sure he's cut out for the experience, especially since his friends in his own grade seem to be having a lot of fun without him. Will Nate be able to find a balance between the pressures of romance and the pleasures of spending time with his friends? The only thing certain for Nate is that there will be lots of laughter, mischief, and detention

A first time for everything: a true story (First Second, 2023)
"A middle grade graphic memoir based on bestselling author and Caldecott Medalist Dan Santat's awkward middle school years and the trip to Europe that changed his life. Dan's always been a good kid. The kind of kid who listens to his teachers, helps his mom with grocery shopping, and stays out of trouble. But being a good kid doesn't stop him from being bullied and feeling like he's invisible, which is why Dan has low expectations when his parents send him on a class trip to Europe. At first, he's right. He's stuck with the same girls from his middle school who love to make fun of him, and he doesn't know why his teacher insisted he come on this trip. But as he travels through France, Germany, Switzerland, and England, a series of first experiences begin to change him--first Fanta, first fondue, first time stealing a bike from German punk rockers... and first love.--

Baby-sitters club: Logan likes Mary Anne! (Baby-sitters Club (Graphic novels), 8, 1, 2020)
It's the first day of a new school year, and while Mary Anne doesn't know what to expect from the eighth grade, she's looking forward to getting back into the swing of things. One thing she definitely doesn't expect is to meet Logan Bruno, who just moved to Stoneybrook! Logan has a dreamy southern accent, he's awfully cute... and he might be interested in joining the BSC. But the baby-sitters aren't sure if Logan would make a good club member, so they send him on a job with Mary Anne as a test. Logan and Mary Anne hit it off, but Mary Anne isn't sure of where their friendship could go. Life in the Baby-sitters Club has never been this complicated -- or this fun!

Big Nate: Move it or lose it! (Big Nate (Andrews McMeel Pub.), , 1, 2023)
"What's middle school without a crisis? Sixth-grader Nate Wright would love to find out, but the emergencies are piling up fast. A gang of eighth-graders steals Nate's favorite lunch spot. Alan Chen chooses a new name (hint: it begins with N) in a brazen attack on Nate's uniqueness. And when a post-hypnotic suggestion works a little TOO well, the lovable Chad becomes P.S. 38's unlikeliest bully. Is Nate any match for Bad Chad? Can he fly under the radar of no-nonsense hall monitor Kim Cressly? Will he survive the worst movie date ever with drama queen Dee Dee? Find out in Move It or Lose It! With all your favorite characters providing laughs on every page, this all-new collection of Big Nate comics means business!" --Back cover.

Big Nate: nailed it! (Big Nate, ,, 2023)
"You can't win 'em all-- especially when you're slumping sixth-grader Nate Wright. Stuck in a cycle of misfortune, our hero finds an unlikely good luck charm... and suddenly, he can do no wrong! He finds a $20 bill, scores a C+ on his social studies test (nailed it!), and even lands a movie date with the captain of the cheer squad. But the high times can't last forever. Before long, Nate's epic hot streak has gone ice cold, thanks to all-time hair crisis, a great escape by the class gerbil, and a no-holds-barred chess match versus... a CAT. Welcome to the riotous world of Big Nate, where chaos is the default setting and Nate's learning the secret of survival: sometimes it's better to be lucky than good!"--Back cover. Ages 8-12.

Clash (Click, 4, 1, 2021)
"Olive, meet Natasha. There’s a new kid in town! From the moment Natasha sets foot in class, it’s clear she’s one of the coolest kids in sixth grade. Everyone wants to be her friend, including Olive ... but things might not be so easy. Olive tries her best to befriend Nat, but it seems like the only thing they have in common is that they both want to hang out with Olive’s friends! Watching as Natasha gets closer with some of her best buds, Olive can’t help but worry that they’re starting to like Nat more than they like her ... and who could blame them? Nat is just that cool ... and Olive is, well, just Olive.".

Big Nate: Payback time! (Big Nate (Andrews McMeel Pub.), , 1, 2019)
"...Nate develops a mysterious allergy to Mrs. Godfrey, wages epic snowball fights with Teddy and Francis, and even takes a nervous newbie under his wing during detention. But after a disastrous run-in with Randy in the cafetorium, our hero faces a dreaded after-school showdown on the soccer field. Will Nate survive or get kicked around?"--Publisher's description.

Big Nate: Great minds think alike (Big Nate, ,, 2014)
Two heads are better than one, except when they're crashing into each other! But that won't prevent Big Nate and his pals from hatching great ideas for fun. Nate Wright is a wisecracking 11-year-old who knows he's destined for greatness.

Swim team (Harper Alley, an imprint of HarperCollins Publishers, Harper Alley, an imprint of HarperCollinsPublishers, 2022)
"Bree can't wait for her first day at her new middle school, Enith Brigitha, home to the Mighty Manatees--until she's stuck with the only elective that fits her schedule, the dreaded Swim 101. The thought of swimming makes Bree more than a little queasy, yet she's forced to dive headfirst into one of her greatest fears. Lucky for her, Etta, an elderly occupant of her apartment building and former swim team captain, is willing to help"--

Best friends (Friends (Hale), 2, 1, 2019)
Sixth grade is supposed to be perfect. Shannon’s got a sure spot in the in-crowd called The Group, and her best friend is their leader, Jen, the most popular girl in school. But the rules are always changing, and Shannon has to scramble to keep up. She never knows which TV shows are cool, what songs to listen to, and who she’s allowed to talk to. Who makes these rules, anyway? And does Shannon have to follow them? Shannon begins to question whether she wants to remain in the in crowd, in a story about popularity, first boyfriends, and finding a path in life.

Big Nate: thunka, thunka, thunka (Big Nate (Andrews McMeel Pub.), , 1, 2016)
Collects adventures of the self-proclaimed genius Nate Wright as he deals with people who don't understand him, including his annoying older sister, clueless dad, and teachers.

Knights of the lunch table: The battling bands (Knights of the lunch table, 3, 1, 2013)
Artie, Wayne, and Percy enter the Battle of the Bands, hoping for fame and fortune, but since none of them can sing or play an instrument, their only hope of winning is finding the fabled Singing Sword.

Picture day (Brinkley yearbooks, 1, 1, 2023)
"Everyone knows the most stressful day of middle school is picture day! And that's exactly where this yearbook-worthy graphic novel series opener begins: with reinventing yourself, drama, popularity, and the friends who see you through."--

Secret hero society: study hall of justice (DC Comics Secret Hero Society, 1, 1, 2016)
The team behind DC Comics Lil' Gotham takes readers to the halls of Ducard Academy in Gotham City, where a young Batman, Superman, and Wonder Woman start their very own Junior Detective Agency! Young Bruce Wayne is the new kid at Ducard Academy, a prep school for gifted middle school students. Bruce finds out pretty quickly that he doesn't fit in: the faculty seems to not just encourage villainous behavior from its students, but reward it. He makes friends with two other outsiders, farm boy Clark Kent and the regal Diana Prince. The three band together to form a detective squad to find out why all of these extraordinary kids have been brought together at Ducard Academy, and to see just what the faculty is plotting.
vol. 1. Study hall of justice --

Big Nate: Silent but deadly (Big Nate (Andrews McMeel Pub.), , 1, 2018)
Nate's alter ego the Great Nose-In! can smell trouble a mile away.

Chunky (Chunky, ,, 2021)
"In this full-color middle grade graphic memoir for fans of Raina Telgemeier and Jerry Craft, Yehudi Mercado draws inspiration from his childhood struggle with his weight while finding friendship with his imaginary mascot Chunky as he navigates growing up in a working class Mexican-Jewish family"--Publisher marketing.